Social, economic, political and health system and program determinants of child mortality reduction in China between 1990 and 2006: A systematic analysis - Xing Lin Feng; Evropi Theodoratou; Li Liu; Kit Yee Chan; David Hipgrave; Robert Scherpbier; Hana Brixi; Sufang Guo; Wen Chunmei; Mickey Chopra; Robert E. Black; Harry Campbell; et al. (Journal of Global Health, 2012)
Between 1990 and 2006, China reduced its under-five mortality rate (U5MR) from 64.6 to 20.6 per 1000 live births and achieved the fourth United Nation’s Millennium Development Goal nine years ahead of target. This study explores the contribution of social, economic and political determinants, health system and policy determinants, and health programmes and interventions to this success.